Contemporary nutrition - Wardlaw, Gordon M.; Smith, Anne M. 1955-. (Dubuque, IA McGraw-Hill, 2011)
Contemporary Nutrition is designed for students with little or no background in college-level biology, chemistry or physiology. It provides the ideal balance of reliable nutrition information and practical consumer-oriented knowledge. With a friendly writing style, the authors act as the student's personal guide to dispelling common misconceptions and to gaining a solid foundation for making informed nutrition choices. Contemporary Nutrition emphasizes that a population consists of individuals with varying genetic and cultural backgrounds, and these individuals will have varying responses to diet. The knowledge gained from this text will allow students to personalize nutrition information and make smart choices.
Includes index.
Keywords: Nutrition; Nutrition -- Textbooks